PLASMA MEMBRANES OF THE RAT LIVER : Isolation and Enzymatic Characterization of a Fraction Rich in Bile Canaliculi - Song, C. S. (The Rockefeller University Press, 1969)
A method is described for the rapid isolation of a plasma membrane fraction containing a high concentration of intact bile canaliculi from the rat liver. Isolated bile canaliculi retain most of the ultrastructural features exhibited in the intact liver cell. The final fraction contains 5'-nucleotidase activity at approximately the same concentration as that in previous preparations of plasma membranes. In the presence of 0.01 M Mg(++), 5'-nucleotidase exhibits a double pH optimum at pH values of 7.5 and 9.5. The activities of glucose-6-phosphatase and alkaline phosphatase are present in low amounts. Cytochrome P-450 is not detectable. Na(+)-K(+)-activation of ATPase is observed to the extent of 20–36% in about half of the assays. The availability of a method for preparation of intact bile canaliculi should prove useful for studying the biochemical events associated with the transport of bile constituents into canaliculi.